Kajian Pengembangan Etosom sebagai Pembawa Agen NSAID Topikal - Bella Triana; Anan Suparman (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. NSAIDs are widely used in pain and inflammation therapy have side effects on the gastrointestinal tract. Delivery of NSAIDs by the topical route can be chosen to reduce these side effects. The ethosomal vesicle system for topical delivery of NSAIDs can be chosen to enhance percutaneous penetration. This review aims to study the ethosomal formulation strategies as NSAID agents delivery, the effect of the ethosomal system on percutaneous penetration of NSAIDs, and also to study the effect of the ethosomal system on the pharmacological activity of NSAIDs. The study was conducted systematically on several international articles from reputable publishers. NSAID agents that have been formulated into ethosomes, including selecoxib, diclofenac, meloxicam, aceclofenac, etodolac, diflunisal, indomethacin, flurbiprofen, and naproxen. The results showed that NSAID ethosomal formulations that showed good characteristics used phospholipids in the form of phosphatidylcholine with ethanol concentrations range from 20-45%, other alcohols such as propylene glycol could be added to increase entrapment efficiency. The ethosomal system was able to increase percutaneous absorption of NSAIDs, indicated by an increase in flux range from 73.71-2741.94%. The ethosomal system was also able to increase the activity of NSAID agents, indicated by an increase in the inhibition of rat paw edema range from 50-300%. It can be concluded that the development of ethosomal system can increase the pharmacological activity of topical NSAIDs by using appropriate strategy formulation. Abstrak. Obat-obat NSAID yang banyak digunakan untuk menangani nyeri dan inflamasi memiliki masalah efek samping gastrointestinal yang sering terjadi. Pengiriman NSAID dengan rute topikal dapat dipilih untuk mengurangi efek samping tersebut. Sistem vesikel etosom untuk pengiriman topikal NSAID dapat dipilih untuk meningkatkan penetrasi perkutan zat aktif. Penelitian ini bertujuan untuk mengkaji strategi formulasi etosom sebagai pembawa agen NSAID topikal, pengaruh pengembangan sistem etosom terhadap penetrasi perkutan NSAID, dan juga mengkaji pengaruh pegembangan sistem etosom terhadap aktivitas farmakologi NSAID. Kajian dilakukan secara sistematis terhadap sejumlah artikel internasional dari penerbit yang bereputasi. Sudah banyak agen NSAID yang diformulasikan menjadi etosom diantaranya selekoksib, diklofenak, meloksikam, aseklofenak, etodolak, diflunisal, indometasin, flurbiprofen, dan naproksen. Hasil penelitian menunjukkan bahwa formulasi etosom NSAID yang menghasilkan karakteristik yang baik menggunakan fosfolipid berupa fosfatidilkolin dengan konsentrasi etanol berkisar 20-45%, dapat ditambahkan alkohol lain berupa propilenglikol untuk meningkatkan efisiensi penjerapan. Sistem etosom mampu meningkatkan penerasiperkutan NSAID ditandai dengan peningkatan nilai flux berkisar antara 73,71-2741,94%. Sistem etosom juga dapat meningkatkan aktivitas agen NSAID ditandai dengan peningkatan inhibisi edema kaki tikus berkisar antara 50-300%. Dapat disimpulkan bahwa pengembangan sistem etosom mampu meningkatkan aktivitas farmakologi NSAID topikal dengan dengan strategi formulasi yang tepat.